2020 IEEE Visualization Conference (VIS) 2020
DOI: 10.1109/vis47514.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Global South: Equal-Area Projections for Choropleth Maps

Abstract: Choropleth maps are among the most common visualization techniques used to present geographical data. These maps require an equal-area projection but there are no clear criteria for selecting one. We collaborated with 20 social scientists researching on the Global South, interested in using choropleth maps, to investigate their design choices according to their research tasks. We asked them to design world choropleth maps through a survey, and analyzed their answers both qualitatively and quantitatively. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…During the two-year collaboration, we co-designed web-based visual tools to explore their data (e.g. [MLLB20]). Furthermore, we observed that many of the experts owned and used a tablet at work to take notes and draw diagrams.…”
Section: Social Science Domainmentioning
confidence: 99%
“…During the two-year collaboration, we co-designed web-based visual tools to explore their data (e.g. [MLLB20]). Furthermore, we observed that many of the experts owned and used a tablet at work to take notes and draw diagrams.…”
Section: Social Science Domainmentioning
confidence: 99%